Medical Management of Infant Intersex: The Juridico-Ethical Dilemma of Contemporary Islamic Legal Response - Haneef, Sayed Sikandar Shah (Zygon, 2015)
Technological advances in the field of medicine and health sciences not only manipulate the normal human body and sex but also provide for surgical and hormonal management of hermaphroditism (intersexuality). Consequently, sex assignment surgery has not only become a standard care for babies born with genital abnormalities in the West but even in some Muslim states. On the positive side, it goes a long way in saving children born with abnormal genitalia from numerous legal interdictions of the pre-sex corrective surgery. Nevertheless, the larger ethical and legal questions that medical management of genital abnormality raises to some extent have not been adequately appreciated by contemporary Muslim responses. This article, therefore, in principle argues against surgical management of intersexuality during early infancy from the Islamic legal perspective.